On 2-neighbourly irregular fuzzy graphs - Santhimaheswari N.R.; Sekar C. (Utilitas Mathematica, 2018)
In this paper, 2- Neighbourly Irregular fuzzy graphs, 2- Neighbourly totally irregular fuzzy graphs are introduced and compared through various examples. 2- Neighbourly Irregularity on some fuzzy graphs whose underlying crisp graphs are a cycle, a Barbell graph Bn,m, Sub(Bn,m) and a path is studied. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.